2015
DOI: 10.1021/acs.est.5b00530
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic Effects of Perfluorooctanesulfonic Acid in gpt Delta Transgenic System Are Mediated by Hydrogen Peroxide

Abstract: Perfluorooctane sulfate (PFOS), a persistent organic pollutant, has recently been closely linked with an increased risk of tumorigenesis. However, PFOS has yielded negative results in various tests of genotoxicity. The present study aimed to investigate the mutagenic response to PFOS in the gpt delta transgenic mouse mutation system and to illustrate the contribution of hydrogen peroxide (H2O2) to PFOS genotoxicity. Mutations at the redBA/gam loci were determined by Spi(-) assay both in vitro and in vivo. DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…PFOS increased mutation frequencies at redBA/gam gene loci in gpt delta transgenic mouse embryonic fibroblasts (Wang et al., ). PFOS failed to induce DNA strand breaks in SHE cells (Jacquet et al., ) and DNA strand breaks or micronuclei in human HepG2 cells (Eriksen et al., ; Florentin et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…PFOS increased mutation frequencies at redBA/gam gene loci in gpt delta transgenic mouse embryonic fibroblasts (Wang et al., ). PFOS failed to induce DNA strand breaks in SHE cells (Jacquet et al., ) and DNA strand breaks or micronuclei in human HepG2 cells (Eriksen et al., ; Florentin et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…Qiao, Xie, Zhang, Liu, Xie, Huang and Yu [34] suggested that PFASs would restrict microbial growth and gene expression, such as disrupting immune function and cellular structure. Moreover, the potential biological damage of PFOS include the breaks in the DNA strand, genotoxic effects in cells, and alteration of the permeability of cell membranes [39][40][41]. Notably, few researches have reported the effects of PFASs on the cell membrane.…”
Section: Pfass Changed the Soil Microbial Community Compositionmentioning
confidence: 99%
“…We thus speculate that PFOS-induced mutant frequency in λ transgenic medaka may be mediated through adverse effects on liver tissue or more specifically the lipid oxidation in the liver4243. The very recent study that reported PFOS’s mutagenic effect in vitro also observed increased lipid droplets in cells treated with PFOS and demonstrated that PFOS induced DNA double strand breaks and gene mutation was mediated by H 2 O 2 through abnormal peroxisomal fatty acid β-oxidation41. Similar mechanism may underlie PFOS-induced increase of mutant frequency in the transgenic medaka model system and future studies are necessary to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 82%
“…PFOS was thus considered as not mutagenic. More recently, a new study reported that PFOS induced concentration-dependent increases in γ-H2AX foci and mutant frequencies at redBA/gam loci in transgenic mouse embryonic fibroblast cells41, suggesting potential genotoxicity of PFOS in vitro . Interestingly, the same study also reported mutation induction, though non-statistically significant, in the livers of gpt delta transgenic mice upon PFOS treatment41, which further supports our finding that PFOS was mutagenic in vivo .…”
Section: Discussionmentioning
confidence: 99%